Morphology and performance of NR/NBR/ENR ternary rubber composites. (15th December 2016) - Zhao, Xiuying; Niu, Kaijing; Xu, Yong; Peng, Zheng; Jia, Li; Hui, David; Zhang, Liqun
Abstract: Epoxidized natural rubber (ENR) was used as a compatibilizer to prepare ternary composites with natural rubber (NR) and nitrile butadiene rubber (NBR). The morphological, structural, and mechanical properties of the NR/NBR/ENR ternary composites were systematically investigated by using SEM, AFM, TEM, DSC, DMTA, and tensile testing. The NR matrix was the continuous phase, and NBR was the dispersed phase with a size of several micrometers. ENR reduced the aggregation of the NBR phase and improved the compatibility between NR and NBR. According to the rule of "like dissolves like", with increasing polarity, ENR migrated from the NR matrix and was dispersed into the NBR phase or gathered at the interface between NR and NBR. Compared with pure NR, the ternary composites had a higher tan δ at 0 °C and lower tan δ at 60 °C, related to the wet grip and rolling resistance of tread materials, respectively. The results also indicated that the prepared NR/NBR/ENR ternary composites exhibited improved tensile strength and tear strength because of the strain-induced crystallization of NR. Therefore, the NR/NBR/ENR ternary composites are promising high-performance tire tread materials.